2000
DOI: 10.3168/jds.s0022-0302(00)75039-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Administration of Lactobacillus gasseri on Serum Lipids and Fecal Steroids in Hypercholesterolemic Rats

Abstract: The effects of milk and nonfermented milks produced from Lactobacillus gasseri on serum lipids and total bile acids and fecal steroids and microflora were estimated in rats fed cholesterol-enriched diets. Lactobacilli decreased and coliforms increased in feces of the control group; however, the concentrations of fecal lactobacilli remained unchanged when rats were fed nonfermented milks. Fecal coliforms in rats receiving milk and nonfermented milk produced from L. gasseri SBT0270 increased, while rats receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
58
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 28 publications
11
58
2
1
Order By: Relevance
“…This is in contrast with the results obtained by Foo et al (2003a,b) and Loh et al (2003). However, Usman and Hosono (2000) reported that the rats fed with non-fermented milk produced from Lb. gasseri were maintaining a high level of faecal lactobacilli throughout the experimental period.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…This is in contrast with the results obtained by Foo et al (2003a,b) and Loh et al (2003). However, Usman and Hosono (2000) reported that the rats fed with non-fermented milk produced from Lb. gasseri were maintaining a high level of faecal lactobacilli throughout the experimental period.…”
Section: Discussioncontrasting
confidence: 77%
“…plantarum in the diet of rats (Foo et al, 2003a). Usman and Hosono (2000) also reported that non-fermented milk produced from Lb. gasseri significantly reduced serum total cholesterol and low density lipoprotein (LDL) cholesterol, and bile acids of rats.…”
Section: Discussionmentioning
confidence: 96%
“…Usman and Hosono [10] also observed a significant reduction in TC and LDL-C in rats fed L. gasseri. In a more recent study, B. longum SPM1207 isolated from healthy adult Koreans reduced serum TC and LDL-C significantly (p <0.05), and slightly increased serum HDL-C in rats [11].…”
Section: Hypocholesterolaemic Effects Of Probioticsmentioning
confidence: 82%
“…In a more recent study, B. longum SPM1207 isolated from healthy adult Koreans reduced serum TC and LDL-C significantly (p <0.05), and slightly increased serum HDL-C in rats [11]. In another study, Shin et al [10] demonstrated that B. longum SPM1207, although killed by sonication, could significantly reduce serum TC and LDL-C, but with no significant improvement in HDL-C when fed to rats for 3 weeks [66]. Kumar et al [67] revealed a 23% reduction in plasma TC, 38% reduction in LDL-C and 19% increase in HDL-C of rats fed with L. plantarum Lp91, a bile salt hydrolase producing strain.…”
Section: Hypocholesterolaemic Effects Of Probioticsmentioning
confidence: 89%
See 1 more Smart Citation